Translation : theory and practice - Zaman, Niaz. (Dhaka : Writers Ink : Distributed by the University Press Ltd., 2013)
Papers presented at the seminar; seminar was organized by PEN Bangladesh.
Includes bibliographical references.
ENH
Keywords: Translating and interpreting -- Bangladesh -- Congresses; Bengali language -- Bangladesh -- Translating -- Congresses; Language and languages -- Sociological aspects -- Congresses; Sociolinguistics -- Congresses; Creative thinking -- Congresses